Current psychological distress and coping strategies reported by university staff in reaction to the COVID-19 pandemic - Sekese, Deneo Nande (Rhodes University, Faculty of Humanities, Department of Psychology)
The COVID-19 pandemic and the subsequent disruptions brought about by the implementation of non-pharmaceutical interventions, provide an unfortunate but useful opportunity to explore employee wellness in response to a crisis, within the Higher Education context. COVID-19 lockdowns meant that university students could no longer access conventional learning through physical attendance at lectures. In response, university staff had to contend with a number of changes to their work environment. These included adapting teaching, learning, and assessment methods to an online platform, which led to changes in job roles, expectations, and increased workload for both academic and support staff. The focus of this research was to explore correlations between the current psychological distress that university employees are experiencing and their recalled coping strategies and sense of coherence in response to the COVID-19 pandemic. A mixed-method approach using a survey design was used. Surveys were completed by 171 university academic and support staff using the SA CORE-10 and BRIEF Cope, as well as qualitative questions. Results demonstrated that higher levels of current psychological distress correlated positively with avoidant coping strategies, particularly in academic staff as opposed to support staff, while more adaptive coping strategies tracked with a sense of coherence.
Keywords: Clinical health psychology; Salutogenesis; Distress (Psychology); Adjustment (Psychology); COVID-19 Pandemic, 2020- -- Influence; College teachers; Sense of coherence